Tahfidz Al-Qur'an Learning Strategy in Increasing the Achievement of Tafsir Learning - Maria, Lucas; Scoot, Amant; Jo, Servais (Journal Neosantara Hybrid Learning, 2023)
Interest in memorizing the Qur'an is increasing until the Board of Education that organizes tahfidz appears. Many parents send their children to the educational institution of tahfidz Al-Qur'an. However, in reality, many of those who memorize the Qur'an complain that they have difficulty memorizing the Qur'an. This research aims to discover the Learning Strategy of Tahfidz Al-Qur'an in Improving the Performance of Tafsir Lessons. The learning strategy is aimed at male and female students at Boarding School Islamic Tarbiyah to improve the performance of tafsir lessons. This research method uses qualitative research. Data collection using observation, interviews and documentation through mobile devices. The results of this research show that (1) the strategy of hifdzil jadid in improving the quality of memorization of santri is memorizing with the tahfidz method and depositing with the talaq method, (2) the strategy of muraja'ah hifdzil jadid in improving the memorization of santri is muraja'ah using the taqrir method by holding mudarosah activities with sima'an between students (3) hifdzil qodim's murojah strategy in improving the quality of students' memorization is independent murojah using the taker method.Strategy